Initial digital vasculitis in a large multicenter cohort of childhood-onset systemic lupus erythematosus - Sakamoto, Ana Paula [UNIFESP] (2017)
Objectives: To assess clinical digital vasculitis (DV) as an initial manifestation of childhood onset systemic lupus erythematosus (cSLE) within a large population. Methods: Multicenter cross-sectional study including 852 cSLE patients (ACR criteria) followed in ten Pediatric Rheumatology centers in Sao Paulo State, Brazil. Results: DV was observed in 25/852 (3%) cSLE patients. Periungual hemorrhage was diagnosed in 12 (48%), periungual infarction in 7 (28%), tip finger ulceration in 4 (16%), painful nodules in 1 (4%) and gangrene in 1 (4%). A poor outcome, with digital resorption, occurred in 5 (20%). Comparison of patients with and without DV revealed higher frequency of malar rash (80% vs. 53%, p = 0.008), discoid rash (16% vs. 4%, p = 0.017), photosensitivity (76% vs. 45%, p = 0.002) and other cutaneous vasculitides (80% vs. 19%, p <0.0001), whereas the frequency of overall constitutional features (32% vs. 61%, p = 0.003), fever (32% vs. 56%, p = 0.020) and hepatomegaly (4% vs. 23%, p = 0.026) were lower in these patients. Frequency of female gender, severe multi-organ involvement, autoantibodies profile and low complement were alike in both groups (p >0.05). SLEDAI-2K median, DV descriptor excluded, was significantly lower in patients with DV compared to those without this manifestation [10 (0-28) vs. 14 (0-58), p = 0.004]. Visceral vasculitis or death were not observed in this cSLE cohort. The frequency of cyclophosphamide use (0% vs. 18%, p = 0.014) was significantly lower in the DV group. Conclusion: Our large multicenter study identified clinical DV as one of the rare initial manifestation of active cSLE associated with a mild multisystemic disease, in spite of digital resorption in some of these patients. (C) 2017 Published by Elsevier Editora Ltda.